Adenoid ameloblastoma with dentinoid is molecularly different from ameloblastomas and adenomatoid odontogenic tumors. (29th September 2021) - Coura, Bruna Pizziolo; dos Santos, Jean Nunes; Fonseca, Felipe Paiva; Bernardes, Vanessa Fátima; de Aquino, Sibele Nascimento; Jorge Júnior, Jacks; Vargas, Pablo Agustin; Romañach, Mário José; de Andrade, Bruno Augusto Benevenuto; Gomez, Ricardo Santiago; Gomes, Carolina Cavalieri
Abstract: Background: Adenoid ameloblastoma is a rare epithelial neoplasm, histologically characterized by the presence of ameloblastoma‐like features, duct‐like structures, epithelial whorls, and cribriform architecture. Dentinoid material is usually present. Some advocate adenoid ameloblastoma is an ameloblastoma variant. However, there are overlapping features not only with ameloblastoma, but also with adenomatoid odontogenic tumor. Most ameloblastomas are characterized by the presence of BRAF p.V600E mutations and adenomatoid odontogenic tumors harbor signature KRAS mutations. The molecular features of adenoid ameloblastoma remain unknown. Methods: Nine adenoid ameloblastoma cases were screened by TaqMan allele‐specific qPCR to assess BRAF p.V600E, ameloblastoma signature mutation, and KRAS p.G12V and p.G12R, adenomatoid odontogenic tumor signature mutations. Results: BRAF and KRAS mutations were not detected in any of the adenoid ameloblastoma cases. Conclusion: The molecular results support adenoid ameloblastoma as an entity distinct from adenomatoid odontogenic tumor and ameloblastoma.